Efektifitas Penggunaan Sosial Media Untuk Meningkatkan Produk UMKM Semprong Djatirasa Karawang - Muhammad Agil Hamid; Uus MD Fadli (Global Leadership Organizational Research in Management, 2024)
This research aims to provide a deeper understanding of how the use of social media platforms can influence consumer behavior and contribute to the growth of the MSME business. This research uses a qualitative approach method, because this qualitative method is a research method that produces descriptive data that forms some written or spoken words from an individual B. Place and Time This research was conducted at umkm semprong djatirasa location jl.akiff ps.blok.gg.karya tani no.21 rt/rw 03/10 karangpawitan kec.karawang barat, karawang jawa barat 41315 From the results of interviews with respondents, it can be concluded that the use of social media has a significant role in their daily lives. Social media not only serves as an entertainment platform, but also as an important source of information as well as a tool to establish relationships and interact professionally,In addition, the conclusion of the respondents' responses to the effectiveness of social media in increasing product sales shows diverse viewsStudents consider social media an integral part of their lives due to their familiarity with it. Instagram, Whats up, Line, Facebook, and Youtobe are the social media used by students. Instagram, Whats up, and Youtobe are the most widely used, with Line and Facebook being the least used.